(untitled) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-1-47-57 The dialogical fragment of text is a part of prose fiction, where responses (characters’ speech) and remarks (author’s speech) represent the communication between characters. The characters’ dialogue may include the description of nonverbal components that make fictional dialogue closer to the natural one due to the constant presence of nonverbal components in the oral communication. In this article the ways of including the nonverbal components of characters’ communication have been analyzed. The remarks accompanying the characters’ words may be placed in the different parts of dialogue according to the characters’ responds. The nonverbal components are more often included in the interpositive and postpositive remarks and are located after the verb with the meaning of the speaking process which is obligatory for the structure of the remark. The verbs, gerunds, verb and noun phrases represent the nonverbal components in the text. The remarks that accompany the characters’ speech of the dialogical fragments of text represent the characters’ emotional state and feelings (laughter, crying, wonder, joy, dryness, contempt). In the work the description of the nonverbal components that accompany the characters’ speech may be correlated with the author’s description of the character out of the communication. It contributes to the creation of the holistic artistic images. Key words: dialogical fragment of text, response, remark, nonverbal components, images of characters